Karakteristik Mineral Batuan Pada Daerah Manifestasi Mata Air Panas Menggunakan SEM-EDAX Dan FTIR Di Desa Candirejo Kecamatan Modayag Kabupaten Bolaang Mongondow - Indra S. J. Oping; Treesje K. Londa; Donny R. Wenas (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2023)
Petrogenesis is a branch of petrology dealing with all aspects of rock formation from the source, primary process, as well the changes (secondary process) occurring on rocks. The study aimed to determine the mineral element composition and rock mineral types in geothermal manifestation area using SEM-EDAX and FTIR in Candipuro Village Modayag Sub-district. Based on research done at Physics laboratory at Universitas Negeri Manado indicated that mineral element compositions contained in Candipuro Village Modayag Sub-district were Silica (Si), Aluminum (Ai), Molybdenum (Mo), Titanium (K), Niobium (Nb), Bromine (Br), Potassium (K), and Calcium (CA), as well mineral types were albite, quartz, magnetite, and gibbsite.